2016
DOI: 10.11138/ccmbm/2016.13.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite in total hip arthroplasty. Our experience with a plasma spray porous titanium alloy/hydroxyapatite double-coated cementless stem

Abstract: SummaryPurpose. Total hip arthroplasty could fail due to many factors and one of the most common is the aseptic loosening. In order to achieve an effective osseointegration and reduce risk of lossening, the use of cemented implant, contact porous bearing surface and organic coating were developed. Aim of this study was to evaluate clinical and radiological mid-term outcomes of a porous titanium alloy/hydroxyapatite double coating manufactured cementless femoral stem applied with "plasma spray" technique and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
2
6
0
1
Order By: Relevance
“…Our findings also confirmed the excellent short- to midterm outcomes reported in another previous study regarding the same prosthetic femoral implant used in younger patients [ 35 ]. Castellini et al reported no cases of stem aseptic loosening or periprosthetic fractures, with an excellent implant survival rate (100%) with stem revision for any reason after a mean follow-up of 4 years [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings also confirmed the excellent short- to midterm outcomes reported in another previous study regarding the same prosthetic femoral implant used in younger patients [ 35 ]. Castellini et al reported no cases of stem aseptic loosening or periprosthetic fractures, with an excellent implant survival rate (100%) with stem revision for any reason after a mean follow-up of 4 years [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also confirmed the excellent short- to midterm outcomes reported in another previous study regarding the same prosthetic femoral implant used in younger patients [ 35 ]. Castellini et al reported no cases of stem aseptic loosening or periprosthetic fractures, with an excellent implant survival rate (100%) with stem revision for any reason after a mean follow-up of 4 years [ 35 ]. In comparison with the study conducted by Castellini et al our study included a larger cohort of implants from three large-volume centers, longer follow-up, a higher mean patient age, and a study population at a greater risk for perioperative complications, in order to investigate the safety and effectiveness of the same plasma-sprayed femoral stem in worse conditions with more serious indications.…”
Section: Discussionsupporting
confidence: 91%
“…Гидроксиапатит обладает способностью не только увеличивать первичную фиксацию имплантатов за счет высокого коэффициента трения и большой прочности на сдвиг, но и усиливать минерализованный рост кости на границе с имплантатом [59]. Еще в 1990-е гг.…”
Section: гидроксиапатитовое покрытиеunclassified
“…1 However, the linear increase of aseptic implant loosening have become the most common complication after the third year, especially in patients with osteoporosis. 2 Lack of sex hormones, glucocorticoids application, and disuse constitute the main causes of osteoporosis. In order to solve this problem, numerous effective methods such as hydroxyapatite-coated titanium (HA-Ti) implants for enhancing osseointegration have been carried out.…”
Section: Introductionmentioning
confidence: 99%